Performance analysis of two-way DF relay selection techniques - Samer Alabed (ICT Express, 2016)
This work proposes novel bi-directional dual-relay selection techniques based on Alamouti space-time block coding (STBC) using the decode and forward (DF) protocol and analyzes their performance. In the proposed techniques, two- and the three-phase relaying schemes are used to perform bi-directional communication between the communicating terminals via two selected single-antenna relays that employ the Alamouti STBC in a distributed fashion to achieve diversity and orthogonalization of the channels and hence improve the reliability of the system and enable the use of a symbol-wise detector. Furthermore, the network coding strategy applied at all relays is not associated with any power wastage for broadcasting data already known at any terminal, resulting in improved overall performance at the terminals. Our simulations confirm the analytical results and show a substantially improved bit error rate (BER) performance of our proposed techniques compared with the current state of the art.